Paper-based microfluidic chip for rapid detection of SARS-CoV-2 N protein. Issue 1 (1st January 2022) - Sun, Mingdi; Han, Man; Xu, Shengnan; Yan, Kai; Nigal, Gul; Zhang, Tongyang; Song, Bo
ABSTRACT: This research has developed a method for rapid detection of SARS-CoV-2 N protein on a paper-based microfluidic chip. The chitosan-glutaraldehyde cross-linking method is used to fix the coated antibody, and the sandwich enzyme-linked immunosorbent method is used to achieve the specific detection of the target antigen. The system studied the influence of coating antibody concentration and enzyme-labeled antibody concentration on target antigen detection. According to the average gray value measured under different N protein concentrations, the standard curve of the method was established and the sensitivity was tested, and its linear regression was obtained. The equation is y = 9.8286x+137.6, R2 = 0.9772 > 0.90, which shows a high degree of fit. When the concentration of coating antibody and enzyme-labeled antibody were 1 μg/mL and 2 μg/mL, P > 0.05, the difference was not statistically significant, so the lower concentration of 1 μg/mL was chosen as the coating antibody concentration. The results show that the minimum concentration of N protein that can be detected by this method is 8 μg/mL, and the minimum concentration of coating antibody and enzyme-labeled antibody is 1 μg/mL, which has the characteristics of high sensitivity and good repeatability.